2016
DOI: 10.1182/blood.v128.22.1219.1219
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fusion Genes at CML Diagnosis Reveal a Complex Pattern of Genomic Rearrangements and Sequence Inversions Associated with the Philadelphia Chromosome in Patients with Early Blast Crisis

Abstract: Introduction The emergence of next generation RNA sequencing (RNA-Seq) technologies will likely advance diagnostic, prognostic and therapeutic strategies for patients (pts) with various cancers.Novel fusions have recently been described in AML and solid tumors using RNA-Seq, and many were out-of-frame.It is not known whether novel fusions are generated at diagnosis (Dx) of CML and if so, their impact on treatment outcome. We used RNA-Seq coupled with whole exome sequencing to identify and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One recent study suggested the presence of novel fusions in the MLL gene and in the ANKRD11 gene in patients with CML-BP, using RNA sequencing. 21 Previously, ABL, RUNX1, ASXL1, 22 and IDH1 mutations were described in patients with CML-BP 23 ; however, paired sample analysis from several patients receiving TKI therapy was not reported. In contrast, the presence and type of ABL kinase domain mutations were found to have minimal prognostic consequences, as we had previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study suggested the presence of novel fusions in the MLL gene and in the ANKRD11 gene in patients with CML-BP, using RNA sequencing. 21 Previously, ABL, RUNX1, ASXL1, 22 and IDH1 mutations were described in patients with CML-BP 23 ; however, paired sample analysis from several patients receiving TKI therapy was not reported. In contrast, the presence and type of ABL kinase domain mutations were found to have minimal prognostic consequences, as we had previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study also demonstrate a very high incidence of clonal evolution, which is more frequently observed than ABL kinase domain mutations, suggesting that transformation is the result of complex molecular processes rather than the mere development of resistance to a TKI. One recent study suggested the presence of novel fusions in the MLL gene and in the ANKRD11 gene in patients with CML‐BP, using RNA sequencing . Previously, ABL, RUNX1, ASXL1 , and IDH1 mutations were described in patients with CML‐BP; however, paired sample analysis from several patients receiving TKI therapy was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Major route ACAs may also help identify patients at greater risk of progression [53]. Some biological factors have also been proposed in single studies (e.g., germline variants in ASXL1 and BIM genes [176,177]; CIP2A protein levels at diagnosis [178]). So far, however, no validated prediction algorithm has ever been derived that may soundly predict who will develop BP.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%